INVESTMENT ASPECTS OF INNOVATIVE DEVELOPMENT OF AGRIBUSINESS - Киценко, В. П. (Scientific Progress & Innovations, 2013)
The necessity of innovation and investment development of agro-industrial complex of Ukraine, as one of the leading sectors of the economy is substantiated. The role of science as a source of innovation is defined. The prospects of biological vector of development of agricultural production in general, and the use of drugs on the basis of beneficial soil microorganisms in particular are highlighted. Innovative advantages of microbial preparations use as industrial means whose value increases especially in the economic crisis are presented. On an example of a specific innovation project the effectiveness of investments in the production of agricultural microbiology is investigated.